Good help: a model for providing in-consultation supervision of general practice trainees. Issue 2 (4th March 2021) - Sturman, Nancy; Fitzmaurice, Liz; Lee, Cathy; Sheldrake, Michelle; Ingham, Gerard
ABSTRACT: Timely clinical supervision of trainee consultations plays a key role in ensuring the safety of patients under the care of general practice trainees, and in trainee learning and professional development. Trainee requests for assistance during their consultations present supervisors with a number of challenges, however, and a number of factors act as barriers to, or reduce the utility of, this in-consultation assistance from the trainee's perspective. Face-to-face supervision in the presence of the patient presents particular challenges and opportunities. It is important to address barriers to trainee help-seeking and improve both trainee and supervisor skills in promoting safe, effective and efficient in-consultation supervision. We introduce a model (β-LACTAM) to assist supervisors in planning and delivering their face-to-face in-consultation supervision. The recent evidence which informed the development of this model is outlined, and some preliminary findings from a pilot of β-LACTAM in Australian general practice training are presented.